2000
DOI: 10.1002/1096-9098(200007)74:3<185::aid-jso4>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum and tissue carcinoembryonic antigen for the prognosis of gastric carcinoma patients

Abstract: These data suggest that preoperative serum CEA levels and staining for CEA in gastric carcinoma tissue sections may have a predictive value in determining prognostic information for patients with resectable gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
3
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 29 publications
4
29
3
2
Order By: Relevance
“…CEA is also well known as a tumour marker in gastric cancer. It has been reported that serum levels and tissue expression of this protein correlate with evidence of tumour progression, such as lymph node metastasis, in keeping with our results (Kojima et al, 1984;Nakane et al, 1994;Kim et al, 2000). Nonspecific crossreacting antigen is a member of the CEA family …”
Section: Discussionsupporting
confidence: 92%
“…CEA is also well known as a tumour marker in gastric cancer. It has been reported that serum levels and tissue expression of this protein correlate with evidence of tumour progression, such as lymph node metastasis, in keeping with our results (Kojima et al, 1984;Nakane et al, 1994;Kim et al, 2000). Nonspecific crossreacting antigen is a member of the CEA family …”
Section: Discussionsupporting
confidence: 92%
“…Originally named for their transforming activities in in vitro assays, TGF-bs now unequivocally demonstrate both tumor suppressor and oncogenic activities. In the current paradigm, the suppressor activities dominate in normal tissue, but during tumorigenesis, changes in TGF-b expression and cellular responses tip the balance in favor of its oncogenic activities (Kim DY et al, 2000;Kim S-J et al, 2000;Wakefield and Roberts, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…CEAs are widely used clinically as tumor markers, specifically for the detection of colorectal carcinoma after surgical resection (Chevinsky, 1991). Many different types of tumors (about 50% of all human tumors) show overexpression of CEAs (Chevinsky, 1991;Kim DY et al, 2000;Kim S-J et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…CEA was strongly associated with the T factor [29,30,33,37], [11] analyzed 68 patients with stage IV gastric cancer using multivariate analysis and concluded that an elevated CEA level was an independent risk factor for predicting liver metastases. A few reports have shown a significant association between elevated CEA and peritoneal metastases [18,34].…”
Section: Ceamentioning
confidence: 99%
“…A few reports have shown a significant association between elevated CEA and peritoneal metastases [18,34]. Although several reports showed that elevated CEA was significantly associated with differentiated tumor types [7,10,48,61], a few reports indicated an association with poorly differentiated types of tumors [29]. Maehara et al analyzed the CEA levels in 221 patients with welldifferentiated gastric cancer.…”
Section: Ceamentioning
confidence: 99%